2014
DOI: 10.1136/bjophthalmol-2013-304081
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and causes of vision loss in sub-Saharan Africa: 1990–2010

Abstract: The age-standardised prevalence of blindness and MSVI decreased substantially from 1990 to 2010, although there was a moderate increase in the absolute numbers with blindness or MSVI. Significant subregional and gender disparities exist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
71
1
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(81 citation statements)
references
References 13 publications
2
71
1
7
Order By: Relevance
“…Similar studies reported refractive error as the third [6,19], second [4] and commonest [11,17,20] cause of ocular morbidity. In a study by Kumah et al [13] in Ghana, the most prevalent condition was refractive error (26.30%).…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Similar studies reported refractive error as the third [6,19], second [4] and commonest [11,17,20] cause of ocular morbidity. In a study by Kumah et al [13] in Ghana, the most prevalent condition was refractive error (26.30%).…”
Section: Discussionmentioning
confidence: 66%
“…Similarly, Adeoye and Omotoye [4] reported figures of 26% for cataract and 10.9% for glaucoma in a study in south west Nigeria. Amadi et al [12] however reported less than 5% for both disease conditions. This difference may due to the fact that their study had a mean age of 30.5 years while the mean age for this study was 45.99 years.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…1,2 Global and regional prevalence of low vision is on the increase, 3,4,5 making it an important public health issue. The challenge of managing low vision is enormous with huge economic implications.…”
Section: Introductionmentioning
confidence: 99%
“…While Africa hosts 11.9% of the World population, it also disproportionately accounts for about 15% of those avoidably blind. Sub-Saharan Africa carries the worse burden with 4.8 million blind partly due to 66% population growth [5]. Other factors accounting for this include scarcity of eye care personnel, limitation in technology and training for eye care, lack of local production of eye medicine, and other consumables leading to dependency on importation in the presence of limited foreign exchange availability, unrestrained and unregulated malpractices of quacks, and traditional eye care providers.…”
Section: Introductionmentioning
confidence: 99%